2002
DOI: 10.1002/jnr.10469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tumor necrosis factor‐alpha central administration on hippocampal damage in rat induced by amyloid beta‐peptide (25–35)

Abstract: Male Wistar rats received unilateral intrahippocampal injections of 3 nmol (3.18 microg) aggregated Abeta(25-35), intracerebroventricular bilateral injections of 0.5 microg human recombinant TNFalpha or both (Abeta(25-35) + TNFalpha-treated animals). Seven days after the surgery brain sections were stained with cresyl violet (Nissl), for fragmented DNA (TUNEL), glial fibrillar acidic protein (GFAP) and isolectin B4-reactive microglia. In addition, caspase-3 activity in brain regions was measured fluorometrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…They demonstrated that A␤ and A␤ [25][26][27][28][29][30][31][32][33][34][35] induce apoptosis through caspase-dependent pathways. [41][42][43][44][45][46][47] In vivo, 1 week after A␤ [25][26][27][28][29][30][31][32][33][34][35] , an increase in caspase-3 activity in the hippocampus of rats 9 and increases in levels of pro-caspases 9, 12, and 3 in the hippocampus of mice 11 were observed. In the present study, we observed increases in pro-and cleaved forms for caspase-9 (mitochondrial stress marker) and caspase-12 (endoplasmic reticulum stress marker) in all structures except the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that A␤ and A␤ [25][26][27][28][29][30][31][32][33][34][35] induce apoptosis through caspase-dependent pathways. [41][42][43][44][45][46][47] In vivo, 1 week after A␤ [25][26][27][28][29][30][31][32][33][34][35] , an increase in caspase-3 activity in the hippocampus of rats 9 and increases in levels of pro-caspases 9, 12, and 3 in the hippocampus of mice 11 were observed. In the present study, we observed increases in pro-and cleaved forms for caspase-9 (mitochondrial stress marker) and caspase-12 (endoplasmic reticulum stress marker) in all structures except the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of neurons in the different hippocampal fields were counted as described previously. 9,10,13 Counting was performed using a light microscope (Leica DMR). Digitized images were acquired using a 40ϫ objective and were analyzed with ImageJ software.…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it must be noted that the phenomenon only occurred when the production of the cytokines was unregulated or when high physiological concentrations of the cytokines were chronically administered in the CNS, and this has been supported by another study. 22 Indeed, other reports have shown that these cytokines can be neuroprotective during ischemia or cranial trauma when synthesized within physiological concentrations 23,24 while their overexpression causes neurodegeneration. 25 Moreover, it has been suggested that TNF-a is neuroprotective when it interacts with TNF-R2, whereas the cytokine induces neurodegeneration when it binds TNF-R1.…”
Section: Innate Immunity and The Central Nervous Systemmentioning
confidence: 99%
“…Intrahippocampal injection of fibrillar Aβ induced direct lesions of the hippocampus, specifically CA1 field [48,49]. However, it also resulted in decreases in the medial septal ChAT and glutamate immunoreactive neurons as compared to controls.…”
mentioning
confidence: 93%